2014
DOI: 10.1002/chem.201302708
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Orthogonality in the Cleavage Process of Closely Related Chelating Protecting Groups for Carboxylic Acids by Using Different Metal Ions

Abstract: Three structurally related relay protecting groups for carboxylic acids that are based on chelating amines have been developed. These protecting groups can easily be introduced by coupling the carboxylic acid and the corresponding amine in the presence of 2-(1H-benzotriazole-1-yl)-1,1,3,3-tetramethyluronium tetrafluoroborate (TBTU). In addition to being stable to a whole array of reaction conditions, these protecting groups are also stable under acidic and basic conditions, allowing them to be used in combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 8 publications
2
21
0
Order By: Relevance
“…[15][16][17][18][19][20][21] In addition, the cleavage can proceed in an intramolecular fashion and give γ-, δ-and ε-lactones in moderate to high yields. [22] Figure 1: Parameters for the quantitative description of the (non-)/planarity of amides; a) twist angle τ, b) Winkler-Dunitzparameter χ N .…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…[15][16][17][18][19][20][21] In addition, the cleavage can proceed in an intramolecular fashion and give γ-, δ-and ε-lactones in moderate to high yields. [22] Figure 1: Parameters for the quantitative description of the (non-)/planarity of amides; a) twist angle τ, b) Winkler-Dunitzparameter χ N .…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…The obtained values with the different salts are a reflection of the stability of the chelation as already observed in earlier studies concerning methanolysis of chelating amides with different metal salts. [8][9][10] These data also revealed that the bpa unit forms more-stable complexes with copper salts. Hence, we surmised that there would be a stronger activation when the complexes with CuCl, CuCl 2 , or Cu(OTf) 2 were applied.…”
Section: Ring-closing Metathesis Reactionsmentioning
confidence: 73%
“…For this purpose, we have synthesized new Hoveyda-Grubbs-type metathesis catalysts bearing chelating units [bpa (10) or dmepa (11)] in their vicinity. By the individual complexation of the latter with different metal salts (Fe 3+ , Zn 2+ , Ag + , Cu + , and Cu 2+ ) we could induce an electron-withdrawing effect that resulted in higher activity of the catalyst.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The product was isolated as a white solid (55.5 mg, 86%). 13 C-NMR major rotamer: 13 (14). 43 The general procedure A was followed with a total reaction time of 1 hour (including 30 min oxidation with DDQ).…”
Section: General Methodsmentioning
confidence: 99%